Pengungkapan Laporan Keuangan Konsolidasi Berdasarkan PSAK 4 Pada PT.Telekomunikasi Indonesia Tbk. - Putri Afrilia; M. Rizal Dika Putra; Ratih Kusumastuti (Universitas 45 Surabaya, 2023)
This study aims to understand the disclosure requirements of consolidated financial statements based on PSAK 4 at PT.Telekomunikasi Indonesia Tbk. This research is a qualitative research using descriptive analysis method and comparative analysis. Based on the results of this study it was concluded that the combined report of PT Telekomunikasi Indonesia Tbk was prepared in accordance with the 2009 revised PSAK 4 which refers to the combined and separate financial statements. In addition, it is ensured that all companies listed on the Indonesia Stock Exchange (IDX) have prepared their financial statements in accordance with accounting standards in force in Indonesia and regulations stipulated by the Financial Services Authority (OJK).